Effect of two insect meals on the gut commensal microbiome of healthy sea trout (Salmo trutta vr. trutta) - Agata Józefiak; Mateusz Rawski; Bartosz Kierończyk; Damian Józefiak; Jan Mazurkiewicz (BMC Veterinary Research, 2023)
Abstract Background The balance of the intestinal commensal microbiome of fish and other animals plays an important role in the physiological processes of healthy animals, contributes to the defense against pathogens, stimulates the immune system and facilitates nutrient metabolism. In the last decade, the interest in the application of the insects in fish nutrition increased, although little is known regarding the effects of insect meals on the gastrointenstinal tract microbiome of the sea trout fingerlings. The aim of this study was to evaluate the effect of two diets containing mealworm (MW) and superworm (SW) on the microbiome of the digesta of sea trout fingerlings and the relative abundances of different taxa among communities under controlled conditions. Results The insect meals produced a similar weight gain and survival rate to sea trout fed fishmeal. The most abundant bacterial phylum in all the treatment groups was Firmicutes followed by Proteobacteria and Actinobacteria, and significant differences in the amount of Cyanobacteria were observed in the SW group. Conclusions The insect meals did not produce differences in the three most abundant phyla in the sea trout digesta. However, the effect of each type of meal on the lower taxonomic levels was evident, particularly in the case of the superworm meal. These microbiome differences indicated that mealworm meal was more related to fishmeal than superworm meal. Our results highlight the potential effects of insect meals, such as mealworm and superworm meals, on the microbiota of sea trout.